Kurdish Women's Identity and Feminism - Karimi, Adel (Sulaimani Journal for Humanities, 2026)
The invasion of ideologies towards Kurdistan has had a significant impact on the socio-political structure of Kurdistan. One of these ideologies is feminism. How do women's thinkers and activists in Kurdistan define the identity of Kurdish women as feminism in Kurdistan? By looking at the socio-political changes from the late 19th century to the 20th century, the dimensions of the conflict between the structure of Kurdish society and ideologies are identified. The incomplete import of feminism from different paradigms and centers of power and attempts to impose them on women's identity in Kurdistan has led to intellectual complexity and disorder of civil activity. To overcome this complexity, the Kurdish researcher must go through social history, interpret the role, mind and attitude of women in Kurdistan and determine the identity of Kurdish women. Then, by cleaning up the ideology of feminism from the centers of power that dominate Kurdistan and linking it to women's identity, it establishes Kurdish feminism as a cognitive institution. This article focuses on 1- Kurdistan analysis unit for the scope of research and interpretation of social phenomena and losses in the field of women, 2- Integration of science and knowledge produced in different parts of the world for knowledge infrastructure It identifies science as the basic points of Kurdish feminism.
Keywords: Kurdish Womens Identity; Imported Feminism; Kurdish Feminism